Adolescent Asthma Self‐Management: Patient and Parent‐Caregiver Perspectives on Using Social Media to Improve Care. (December 2013) - Panzera, Anthony D.; Schneider, Tali K.; Martinasek, Mary P.; Lindenberger, James H.; Couluris, Marisa; Bryant, Carol A.; McDermott, Robert J.
ABSTRACT: BACKGROUND: Self‐management of asthma can now leverage new media technologies. To optimize implementation they must employ a consumer‐oriented developmental approach. This study explored benefits of and barriers to improved asthma self‐management and identified key elements for the development of a digital media tool to enhance asthma control. METHODS: Between August 2010 and January 2011, 18 teens with asthma and 18 parent‐caregivers participated in semistructured in‐depth interviews to identify mechanisms for improving asthma self‐management and propose characteristics for developing a digital media tool to aid such efforts. RESULTS: Teens and caregivers enumerated physician‐recommended strategies for asthma management as well as currently employed strategies. Both groups thought of a potential digital media solution as positive, but indicated specific design requirements for such a solution to have utility. Whereas most participants perceived mobile platforms to be viable modes to improve asthma self‐management, interest in having social networking capabilities was mixed. CONCLUSIONS: A digital media product capable of tracking conditions, triggers, and related asthma activities can be a core element of improved asthma control for youth. Improved asthma control will help decrease school absenteeism.